Titanium-based lithium ion sieve and preparation method thereof
By doping cerium-based solid solution and nitrogen elements into the titanium-based lithium ion sieve, a structure with oxygen vacancy is formed, which solves the problems of slow lithium ion migration rate and low adsorption efficiency, and achieves efficient and stable lithium ion adsorption and reuse.
Patent Information
- Application Number
- CN202311843957.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2025-04-18
AI Technical Summary
The existing titanium-based ion sieve has slow migration rate, low adsorption efficiency and high dissolution rate in the adsorbent, which limits its industrial development.
By doping a cerium-based solid solution into a titanium-based lithium ion sieve, a structure with oxygen vacancy is formed, the diffusion rate of lithium ions is improved, and the structural stability and reusability of the adsorbent are improved through nitrogen doping and the addition of pyridine-type nitrogen.
It significantly improves the adsorption efficiency of lithium ions, reduces the dissolution rate, enhances structural stability and reusability, and solves key problems in the prior art.
Smart Images

Figure CN119838554A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorbents, and more specifically, to a titanium-based lithium ion sieve and a preparation method thereof. Background Art
[0002] The growing demand for electric vehicles and the increasing environmental pollution caused by lithium resource extraction have prompted people to seek more efficient lithium recovery technologies. The development and utilization of liquid lithium resources from salt lake brine through adsorption is an important approach at present.
[0003] The adsorption method has the advantages of being green, environmentally friendly, highly selective, and having a high recovery rate, and has attracted much attention. The key to the adsorption method lies in the selection of adsorbents. Among them, lithium ion sieve adsorbents have the advantages of large adsorption capacity, strong selective adsorption, and stable structure, and are considered to be one of the most promising adsorbents for extracting lithium from liquid lithium resources. Among them, the layered titanium ion sieve Li2TiO3 has a high theoretical maximum adsorption capacity, renewability, and selectivity, and can be synthesized by a high-temperature solid-phase method. The process is simple and easy to scale up industrially.
[0004] However, the titanium-based ion sieves in the prior art have problems such as slow migration rate of lithium ions inside the adsorbent, low adsorption efficiency, and high dissolution rate. The above problems have become an important bottleneck in the current industrial development of titanium-based ion sieve adsorbents. Summary of the invention
[0005] An object of the present invention is to provide a titanium-based lithium ion sieve that can solve at least one technical problem of the prior art titanium-based ion sieves, namely, slow migration rate of lithium ions inside the adsorbent, low adsorption efficiency, and high dissolution rate.
[0006] Another object of the present invention is to provide a method for preparing the titanium-based lithium ion sieve.
[0007] In order to achieve the above objectives, the present invention provides the following technical solutions.
[0008] The titanium-based lithium ion sieve according to the first embodiment of the present invention comprises: lithium titanium oxide, and a cerium-based solid solution, wherein the cerium-based solid solution comprises oxygen vacancies, and in the Raman spectrum of the cerium-based solid solution, at 464.8 cm -1 ~465.2cm -1 and 602.8cm -1 ~603.2cm -1 The ratio of the peak intensity at I 603±0.2 / I 465±0.2 =0.05~0.3.
[0009] According to some embodiments of the present invention, the cerium-based solid solution dopes the lithium titanium oxide.
[0010] According to some embodiments of the present invention, the molecular formula of the titanium-based lithium ion sieve is Li2Ti x O3 / (1-x)Ce y M 1- y O2, wherein M is a metal element that forms a solid solution with the cerium-based material, and x and y represent the molar ratio of the elements: x=0.7-0.9, y=0.6-0.95.
[0011] According to some embodiments of the present invention, the titanium-based lithium ion sieve contains nitrogen, and the content of the nitrogen in the titanium-based lithium ion sieve is 1.5at.% to 2.8at.%; and / or the titanium-based lithium ion sieve contains pyridinic nitrogen, and the pyridinic nitrogen accounts for 15% to 30% of the total nitrogen content.
[0012] According to some embodiments of the present invention, the average particle size of the titanium-based lithium ion sieve is 150nm to 200nm; and / or the specific surface area is 15.8m 2 / g~25.3m 2 / g, and / or, the contact angle with 0.05M LiOH aqueous solution is 14° to 28°.
[0013] According to the second aspect of the present invention, the preparation method of the titanium-based lithium ion sieve comprises the following steps: mixing a cerium-based precursor, a titanium source and a lithium source to obtain a solid phase mixture; calcining the solid phase mixture to obtain a titanium-based lithium ion sieve, wherein the titanium-based lithium ion sieve comprises lithium titanium oxide and a cerium-based solid solution, wherein the cerium-based solid solution comprises oxygen vacancies, and in the Raman spectrum of the cerium-based solid solution, at 464.8 cm -1 ~465.2cm -1 and 602.8cm -1 ~603.2cm -1 The ratio of the peak intensity at I 603±0.2 / I 465±0.2 =0.05~0.3.
[0014] According to some embodiments of the present invention, the calcination is performed using a step-by-step calcination process.
[0015] According to some embodiments of the present invention, the method for preparing the cerium-based precursor adopts a sol-gel method or a solution combustion method, and nitrogen doping is performed by providing a nitrogen-containing environment.
[0016] According to some embodiments of the present invention, the cerium-based solid solution is a composite solid oxide composed of Ce and one or more of Ca, Mg, Ni, Co, Zn, La, In, Fe and Zr; and / or the titanium source is one or more of anatase titanium dioxide, rutile phase titanium dioxide, mixed phase titanium dioxide and titanic acid; and / or the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium acetate and lithium citrate.
[0017] According to some embodiments of the present invention, the method for preparing the titanium-based lithium ion sieve further includes the following step: acid washing the titanium-based lithium ion sieve.
[0018] The adsorbent according to an embodiment of the present invention comprises a titanium-based lithium ion sieve, which comprises lithium titanium oxide and a cerium-based solid solution; in the Raman spectrum of the cerium-based solid solution, at (465±0.2) cm -1 and (603±0.2)cm -1 The ratio of the peak intensity at I 603±0.2 / I 465±0.2 = 0.05 to 0.3, that is, the cerium-based solid solution contains oxygen vacancies, and the defect degree of the oxygen vacancies is between 0.05 and 3. When the titanium-based ion sieve provided by the embodiment of the present invention is used as an adsorbent, it has the advantages of high adsorption efficiency, low dissolution rate, stable structure, good reusability, etc.
[0019] Further features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments of the present invention with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.
[0021] Figure 1 This is the SEM image of the product of Comparative Example 3.
[0022] Figure 2 : is a SEM image of the titanium-based lithium ion sieve according to Example 1 of the present invention. DETAILED DESCRIPTION
[0023] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.
[0024] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the invention, its application, or uses.
[0025] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the specification.
[0026] In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0027] It should be noted that like reference numerals and letters refer to similar items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.
[0028] The titanium-based lithium ion sieve according to an embodiment of the present invention is described in detail below with reference to the accompanying drawings.
[0029] The titanium-based lithium ion sieve according to an embodiment of the present invention comprises lithium titanium oxide and a cerium-based solid solution, wherein the cerium-based solid solution comprises oxygen vacancies, and in the Raman spectrum of the cerium-based solid solution, at 464.8 cm -1 ~465.2cm -1 and 602.8cm -1 ~603.2cm -1 The ratio of the peak intensity at I 603±0.2 / I 465±0.2 =0.05~0.3, that is, at (465±0.2)cm -1 and (603±0.2)cm -1 The ratio of the peak intensity at I 603±0.2 / I 465±0.2 =0.05~0.3.
[0030] Among them, solid solution refers to the alloy phase in which the solute atoms are dissolved in the solvent lattice and the solvent type is maintained. The cerium-based solid solution is a solid solution metal element with a radius similar to that of the cerium element doped in the cerium-based material. The oxygen vacancy concentration of the cerium-based solid solution can be effectively controlled by doping with different metal elements or adjusting the ratio between the elements.
[0031] In the embodiment of the present invention, the oxygen defect concentration of the synthesized solid solution material is determined by Raman technology. In the Raman spectrum of the cerium-based solid solution, the oxygen defect concentration at (465±0.2) cm -1 and (603±0.2)cm -1 The peaks at 1 and 2 are respectively attributed to the F2g cubic fluorite structure vibration and oxygen vacancy. The ratio of the peak intensities I 603±0.2 / I 465±0.2 It can indicate the degree of oxygen vacancy defects. Ce-based solid solutions contain oxygen vacancies. In the Raman spectrum, at (465±0.2) cm -1and (603±0.2)cm -1 The ratio of the peak intensity at I 603±0.2 / I 465±0.2 =0.05~0.3. In other words, the cerium-based solid solution has an oxygen defect structure, which can reduce the diffusion barrier of lithium ions. In addition, the oxygen defect structure of the cerium-based solid solution can affect the electronic structure or bond length of the surrounding (lithium titanate) Li-O bonds, change the local coordination environment, and make Li easier to adsorb or desorb, thereby making Li diffusion easier. At the same time, (465±0.2)cm -1 and (603±0.2)cm -1 The ratio of the peak intensity at I 603±0.2 / I 465±0.2 =0.05~0.3In this range, the oxygen defect structure is relatively stable, which can increase the service life of the titanium-based lithium ion sieve.
[0032] It can be seen that the titanium-based lithium ion sieve of the embodiment of the present invention contains a cerium-based solid solution, which is a solid solution system with oxygen vacancies. At the same time, the cerium-based solid solution contains CeO2, which has a typical face-centered cubic fluorite structure. Such a structure will produce octahedral vacancy gaps suitable for ion diffusion, which is very beneficial to the movement of oxygen ions. The cerium-based solid solution can form a structure with oxygen defect sites, and this oxygen defect can accelerate the Li in the solid phase by reducing the diffusion energy barrier. + transfer, thereby promoting the improvement of lithium adsorption performance.
[0033] In addition, the titanium-based lithium ion sieve of the embodiment of the present invention can be used as an adsorbent. When used as an adsorbent, the titanium-based lithium ion sieve of the embodiment of the present invention has the advantages of low dissolution rate, stable structure, good reusability, etc.
[0034] Thus, the adsorbent according to an embodiment of the present invention comprises a titanium-based lithium ion sieve, which comprises lithium titanium oxide and a cerium-based solid solution; in the Raman spectrum of the cerium-based solid solution, at (465±0.2) cm -1 and (603±0.2)cm -1 The ratio of the peak intensity at I 603±0.2 / I 465±0.2 = 0.05 to 0.3, that is, the cerium-based solid solution contains oxygen vacancies, and the defect degree of the oxygen vacancies is between 0.05 and 3. When the titanium-based ion sieve provided by the embodiment of the present invention is used as an adsorbent, it has the advantages of high adsorption efficiency, low dissolution rate, stable structure, good reusability, etc.
[0035] In some specific embodiments of the present invention, the cerium-based solid solution is doped with lithium titanium oxide. The doping of the cerium-based solid solution material rich in oxygen defects can reduce the diffusion barrier of lithium ions and accelerate the Li +transfer, promoting the improvement of lithium adsorption rate.
[0036] According to one embodiment of the present invention, the molecular formula of the titanium-based lithium ion sieve is Li2Ti x O3 / (1-x)Ce y M 1-y O2, where M is a metal element that forms a solid solution with the cerium-based material, and x and y represent the molar ratio of the elements: x = 0.7 to 0.9, y = 0.6 to 0.95. That is, in this embodiment, the molecular formula of the titanium-based lithium ion sieve is Li2Ti x O3 / (1-x)Ce y M 1-y O2, M represents a solid solution element that can form with the cerium-based material, wherein x, y represent the molar ratio of the elements: x = 0.7 to 0.9, y = 0.6 to 0.95. In this embodiment, by using the titanium-based lithium ion sieve of the above molecular formula, good adsorption is achieved.
[0037] It should be noted that the different molar ratios of Ce / M in cerium-based materials can easily affect the structure of the material. In addition to the well-known thermodynamically stable phases, the ratio adjustment also involves some transitional metastable phases. The ratio and activity of lattice oxygen are also different under these phase changes, which have an impact on the lithium migration and adsorption rates. Therefore, limiting the ratio of Ce / M is beneficial to improving the lithium migration and adsorption rates. In addition, if too much cerium-based solid solution is added, it is easy to cause the structure of the titanium-based ion sieve to collapse and affect the cycle life. Therefore, by controlling the content of x, it is beneficial to ensure the cycle life. It can be seen that in this embodiment, the molecular formula of the titanium-based lithium ion sieve is Li2Ti x O3 / (1-x)Ce y M 1-y O2, x=0.7~0.9, y=0.6~0.95.
[0038] According to one embodiment of the present invention, the titanium-based lithium ion sieve contains nitrogen, and the content of nitrogen in the titanium-based lithium ion sieve is 1.5at.% to 2.8at.%; and / or, the titanium-based lithium ion sieve contains pyridinic nitrogen, and the pyridinic nitrogen accounts for 15% to 30% of the total nitrogen content. For example, the decomposition of the cerium-based precursor can provide abundant nitrogen elements for the adsorbent. For another example, the ammonium citrate complexation method and urea combustion method used in the preparation of the cerium-based solid solution can provide a N environment, and this N will be nitrogen-doped during the roasting process, which will have an interface modification effect on the surface of lithium titanate.
[0039] It should be noted that by making the titanium-based lithium ion sieve contain nitrogen, the surface of lithium titanate can be modified. In addition, the macropores left by the gas generated by the nitrogen-containing substance during the calcination process can effectively increase the wettability of the material, and the nitrogen doping provides the adsorbent with abundant nitrogen functional groups (negatively charged groups), which is beneficial to improve the Li + Adsorption. In addition, in this embodiment, the adsorption capacity for lithium ions is synergistically improved through interface modification and oxygen defect engineering.
[0040] In addition, when the titanium-based lithium ion sieve contains pyridinic nitrogen, and the pyridinic nitrogen accounts for 15% to 30% of the total nitrogen content, that is, XPS is used for peak separation to obtain the type of nitrogen in the titanium-based lithium ion sieve. The titanium-based lithium ion sieve of this embodiment contains pyridinic nitrogen (pyridine N), and the pyridinic nitrogen accounts for 15% to 30% of the total nitrogen content, which is beneficial to ensure electronic conductivity.
[0041] In some specific embodiments of the present invention, the average particle size of the titanium-based lithium ion sieve is about 150nm to 200nm; and / or the specific surface area is 15.8m 2 / g~25.3m 2 / g; and / or, has good wettability with 0.05M LiOH aqueous solution, and the contact angle is 14° to 28°. In this embodiment, the average particle size can be obtained by using SEM images, for example, counting the number of particles in the SEM photo and combining the scale to obtain the particle size.
[0042] It should be noted that, firstly, due to the average particle size of titanium-based lithium ion sieve and the cerium-based solid solution doped with lithium titanium oxide, such as Li2Ti x O3 / (1-x)Ce y M 1-y The average particle size of O2 is related to the content change of Li2TiO3 doped with the cerium-based solid solution, that is, the content change of Li2TiO3 doped with the solid solution will lead to the change of the overall particle size, and the corresponding change of the oxygen vacancy concentration. In this embodiment, the average particle size of the titanium-based lithium ion sieve is 150nm to 200nm. For example, the average particle size of the titanium-based lithium ion sieve is 150nm, 155nm, 160nm, 170nm, 180nm, 190nm or 200nm. Within the above range, it is conducive to achieving I 603±0.2 / I 465±0.2 =0.05~0.3.
[0043] Secondly, the specific surface area of the titanium-based lithium ion sieve is 15.8m 2 / g~25.3m 2 / g, for example, the specific surface area of titanium-based lithium ion sieve is 15.8m 2 / g, 16.0m 2 / g, 16.5m 2 / g, 17.0m 2 / g, 18.0m 2 / g, 19.0m 2 / g, 20.0m 2 / g, 22.5m 2 / g or 25.3m 2 / g, etc., which is conducive to the improvement of adsorption rate. It should be noted that if the specific surface area of the titanium-based lithium ion sieve is greater than 25.3m 2 / g, the material surface energy is higher, and it is easy to agglomerate when dispersed in liquid, resulting in a decrease in the utilization rate of the adsorbent; if the specific surface area of the titanium-based lithium ion sieve is less than 15.8m 2 / g, which can easily reduce the active sites of lithium ions adsorbed on the adsorption surface and affect the adsorption effect.
[0044] Again, the contact angle of the titanium-based lithium ion sieve with a 0.05M LiOH aqueous solution is 14° to 28°. For example, the contact angle of the titanium-based lithium ion sieve with a 0.05M LiOH aqueous solution is 14°, 15°, 20°, 25°, 26° or 28°, etc. The titanium-based lithium ion sieve has good wettability with a 0.05M LiOH aqueous solution, which is beneficial to the dispersion and infiltration of the adsorbent in the lithium-containing solution, achieving a better adsorption effect.
[0045] In addition, regarding condition 1: the average particle size of the titanium-based lithium ion sieve is 150nm~200nm; condition 2: the specific surface area is 15.8m 2 / g~25.3m 2 / g; Condition three: the contact angle with 0.05M LiOH aqueous solution is 14° to 28°. One or more conditions can be selected according to different requirements for titanium-based lithium ion sieves.
[0046] The present invention also provides a method for preparing a titanium-based lithium ion sieve, comprising the following steps: mixing a cerium-based precursor, a titanium source and a lithium source to obtain a solid phase mixture; calcining the solid phase mixture to obtain a titanium-based lithium ion sieve, wherein the titanium-based lithium ion sieve comprises lithium titanium oxide and a cerium-based solid solution, wherein the cerium-based solid solution comprises oxygen vacancies, and in the Raman spectrum of the cerium-based solid solution, at 464.8 cm -1 ~465.2cm -1 and 602.8cm -1 ~603.2cm -1 The ratio of the peak intensity at I 603±0.2 / I 465±0.2 =0.05~0.3, that is, at (465±0.2)cm -1 and (603±0.2)cm -1 The ratio of the peak intensity at I603±0.2 / I 465±0.2 =0.05~0.3.
[0047] That is, in this embodiment, when preparing the titanium-based lithium ion sieve, the cerium-based precursor, the titanium source and the lithium source can be mixed to obtain a solid phase mixture, and then the solid phase mixture is calcined to obtain the titanium-based lithium ion sieve. In addition, the prepared titanium-based lithium ion sieve contains lithium titanium oxide and a cerium-based solid solution, the cerium-based solid solution contains oxygen vacancies, and in the Raman spectrum of the cerium-based solid solution, at (465±0.2) cm -1 and (603±0.2)cm -1 The ratio of the peak intensity at I 603±0.2 / I 465±0.2 =0.05~0.3.
[0048] In the embodiment of the present invention, the adsorbent product can be prepared by a solid phase synthesis process and a roasting process. Optionally, the mixing method in the solid phase synthesis process used in the present invention adopts but is not limited to ball milling, sand milling, etc., drying adopts an oven, spray drying, etc., and roasting can adopt an air atmosphere, an inert atmosphere mixed into the method, etc. It should be noted that the solid phase synthesis operation process is simple and easy to scale up in industrial production.
[0049] In addition, in the embodiment of the present invention, a titanium-based lithium ion sieve is obtained by calcination. For example, the solid solution material is not coated on the surface of lithium titanate, but is a composite oxide calcined together with a cerium-based solid solution and lithium titanate. This structure can create defects in Ti, which is beneficial to the adsorption and activation of titanium.
[0050] Optionally, the lithium titanium oxide can be Li2TiO3 or Li4Ti5O2, that is, the preparation method of the present invention can be applied to Li2TiO3 and also to the preparation or modification of spinel titanium oxide Li4Ti5O2. It should be noted that the products prepared by using different lithium titanium oxides can all be applied to Li2Ti x O3 / (1-x)Ce y M 1- y The general molecular formula is O2.
[0051] Optionally, the solid phase mixture is a powder, that is, the preparation method of this embodiment can be applied to the preparation of a powder adsorbent, but it should be noted that it is not limited to being integrated with a carrier or applied to the preparation of other shaped adsorbents. The advantage of powders is that they have a large specific surface area and a high adsorption rate, which is conducive to adsorption, but powders are easy to lose; immobilized or shaped adsorbents can reduce loss, but the pores will be limited and the adsorption effect will be weakened.
[0052] In some specific embodiments of the present invention, the calcination adopts a step-by-step calcination process. In this embodiment, the use of segmented calcination technology is beneficial to the control of the intermediate nucleation stage, and the segmented calcination is beneficial to the generation of more nucleation sites for grains, which can relatively control the growth of grains. For example, the calcination used in this embodiment adopts a step-by-step calcination process, with a pre-calcination temperature of 200°C to 350°C, a heating rate of 2°C / min to 5°C / min, and a pre-calcination constant temperature of 2h to 4h; the calcination temperature is 400°C to 550°C, the heating rate is 2°C / min to 4°C / min, and the calcination time is 5h to 20h. In this embodiment, the above range is used to easily control the content of oxygen defects, nitrogen content and pyridine N content in the solid solution.
[0053] According to one embodiment of the present invention, the preparation method of the cerium-based precursor adopts a sol-gel method or a solution combustion method, and nitrogen doping is performed by providing a nitrogen-containing environment. Nitrogen doping provides abundant nitrogen elements for the adsorbent, which is beneficial to improve its adsorption effect.
[0054] In other words, ammonium citrate is introduced into the sol-gel method, and urea is introduced into the solution combustion method. Ammonium citrate or urea is introduced into the synthesis process of the cerium-based solid solution, and these substances can react with the lithium source (in the raw material for synthesizing lithium titanate) to generate intermediate lithium salts, and then the temperature required for synthesizing lithium titanate with the intermediate lithium salts and the titanium source will be reduced, that is, the synthesis temperature can be reduced, for example, the synthesis temperature can be reduced to within 550°C.
[0055] That is to say, the organic species in the precursor can be ammonium citrate or urea. The presence of the organic species in the precursor can reduce the temperature required for calcination. The operation is simple and convenient, and the adsorbent particles obtained are small in size and evenly distributed. In the embodiments of the present invention, the gel sol method and solution combustion method using ammonium citrate or urea as the organic source are used, but are not limited to other methods for preparing cerium-based materials derived from or involved in two organic sources.
[0056] In addition, since ammonium citrate or urea is introduced during the synthesis of the cerium-based solid solution, these substances can react with the lithium source (in the raw material for synthesizing lithium titanate) to generate intermediate lithium salts. Then, the temperature required for synthesizing lithium titanate with these intermediate lithium salts and the titanium source will be reduced, thereby lowering the synthesis temperature.
[0057] In this embodiment, the cerium-based precursor is introduced by adopting the sol-gel method or the solution combustion method, and other metal elements can be introduced synchronously by rationally utilizing the ionic radius effect or the valence balance theory, which is conducive to forming a solid solution with lattice oxygen defects and a Li2TiO3 composite structure in the subsequent roasting process. Among them, the ionic radius effect or the valence balance theory refers to the doping of the metal element M, which is doped into the CeO2 structure. The process formed after the doping is the process of creating oxygen vacancy defects. In addition, the decomposition of the organic matter of the cerium-based precursor can provide rich nitrogen elements for the adsorbent. N doping is mainly a negative electron group, which has a Li + adsorption effect.
[0058] Optionally, the titanium-based lithium ion sieve contains nitrogen; the nitrogen content is 1.5 to 2.8 at.%, wherein the nitrogen content is analyzed by XPS.
[0059] Optionally, the decomposition of the cerium-based precursor organic matter can provide a porous structure for the adsorbent, which can enhance the wettability of the solution on the adsorbent surface and the active sites for lithium ion contact, further improving the wettability of the adsorbent to the lithium-rich solution.
[0060] In some specific embodiments of the present invention, the cerium-based solid solution is a composite solid oxide composed of Ce and one or more of Ca, Mg, Ni, Co, Zn, La, In, Fe and Zr; and / or the titanium source is one or more of anatase titanium dioxide, rutile phase titanium dioxide, mixed phase titanium dioxide and metatitanic acid; and / or the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium acetate and lithium citrate.
[0061] Among them, when the cerium-based solid solution is a composite solid oxide composed of Ce and one or more of Ca, Mg, Ni, Co, Zn, La, In, Fe and Zr, by adopting the above-mentioned cerium-based solid solution, the oxygen vacancy concentration is adjustable and the structure is stable during the calcination process, which is beneficial to enhancing the cyclic stability of the titanium-based adsorbent.
[0062] When the titanium source is one or more of anatase titanium dioxide, rutile phase titanium dioxide, mixed phase titanium dioxide and metatitanic acid, the titanium source may be but is not limited to anatase titanium dioxide, rutile phase titanium dioxide, mixed phase titanium dioxide and metatitanic acid, etc. By adopting the above titanium sources, it has the advantages of a wide range of sources and is conducive to the generation of a stable lithium titanate structure.
[0063] In addition, when the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium acetate and lithium citrate, the above lithium source can effectively avoid the generation of harmful gases and is conducive to the formation of a stable lithium titanate structure. In addition, when the salt is a nitrate or acetate with good water solubility, the above salt has the advantages of good water solubility and is not easy to generate toxic waste gas during the roasting process.
[0064] According to one embodiment of the present invention, the preparation method of the titanium-based lithium ion sieve further includes the following steps: acid-washing the titanium-based lithium ion sieve. After the titanium-based adsorbent is acid-washed, eluting part of Ti is beneficial to creating lithium adsorption sites. That is to say, in this embodiment, the titanium-based adsorbent is acid-washed to ensure that it has lithium adsorption performance, which is beneficial for the final ion sieve product to have excellent acid corrosion resistance, good structural stability, and longer cycle life.
[0065] The preparation method of the embodiment of the present invention is described in detail below by taking the ammonium citrate complexation method or the urea solution combustion method as an example.
[0066] S1. The cerium-based precursor is synthesized by using the ammonium citrate complexation method or the urea solution combustion method.
[0067] First, the specific steps of using ammonium citrate complexation include:
[0068] S11. Accurately weigh cerium salt and M=Ca according to the molar ratio Ce / M=1:0.2~1 2+ Mg 2+ 、Ni 2+ 、Co 2+ 、Zn 2+ ,La 3 + 、In 3+ , Fe 3+ and Zr 4+ One or more of the salts are fully dissolved in deionized water.
[0069] S12, add ammonium citrate solution (ethanol dissolution, mass fraction of 5% to 20%) dropwise until the molar ratio of metal content to ammonium citrate is 1:1.2 to 1.5, and stir thoroughly.
[0070] S13, evaporating the above solution at 80℃~95℃ until yellow gel appears, then transferring the gel to an oven at 110℃~150℃ for foaming, and drying at a constant temperature for 10h~15h, to obtain a fluffy and porous cerium-based material precursor 1, the pore size of which is 4.5μm~20μm, and the specific surface area of which is 18m 2 / g~45m 2 / g.
[0071] Secondly, the specific steps of using the urea combustion method include:
[0072] S11', the urea combustion method is different from the above in that there is no deionized water dissolution process, and the cerium salt and M=Ca with a molar ratio of Ce / M=1:0.1~0.9 are accurately weighed. 2+ Mg 2+ 、Ni 2+ 、Co 2+ 、Zn 2+ ,La 3+ 、In 3+ , Fe 3+ and Zr 4+ Add urea at the same time with equal salt, and the molar ratio of metal content to urea is 1:1.1-1.35. Grind thoroughly until the mixed solid presents a milky white viscous substance with uniform color.
[0073] S12', the viscous substance in step S11' is transferred to an oven at 120°C to 130°C for drying for 12h to 20h, and a cerium-based material precursor 2 is obtained, the pore size is 2.4μm to 16μm, and the specific surface area is 27m 2 / g~36m 2 / g.
[0074] S2, preparing an adsorbent by using a cerium-based precursor, a lithium source and a titanium source, specifically comprising the following steps:
[0075] S21, the cerium-based precursor (Ce y M 1-y O2) 1 or 2, lithium source, titanium source, dispersant add ethanol to fully grind to obtain a mixed slurry, the mixed slurry is dried and ground to obtain a mixed powder, the titanium source can be but not limited to anatase titanium dioxide, rutile phase titanium dioxide, mixed phase titanium dioxide, metatitanic acid, etc.; the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium acetate, lithium citrate; the lithium source, the total metal of the cerium-based precursor, the Li:M in the titanium source 总 :Ti molar ratio = 2: (0.1 ~ 0.3): (0.9 ~
[0076] 0.7); Ce-based precursor total metal M 总 The total molar fraction of Ti in the titanium source in the adsorption material is 1; the solid content (the proportion of total solid matter in the overall solution during the preparation process) is guaranteed to be 45% to 70%; the dispersant is any one or a mixture of several of PEG200-PEG6000, polyvinyl alcohol, ammonium citrate, etc.; the content is 0.05% to 0.1%.
[0077] S22, the solid powder obtained in step S21 is subjected to a step-by-step sintering process, with a pre-sintering temperature of 200°C to 350°C, a heating rate of 2°C / min to 5°C / min, and a pre-sintering constant temperature of 2h to 4h; the sintering temperature is 400°C to 550°C, a heating rate of 2°C / min to 4°C / min, and a sintering time of 5h to 20h. Among them, the pre-sintering adopts an air atmosphere, and the sintering stage adopts an inert atmosphere; the inert atmosphere is one or a mixture of nitrogen, argon, and helium.
[0078] In step S22, after sintering, the oxygen vacancy concentration index is controlled to be 1 603±0.2 / I 465±0.2 =0.05~0.3 (The oxygen deficiency concentration was determined by using Raman instrument of Renishaw in Via. The peak intensity ratio I 603±0.2 / I 465±0.2 to indicate the degree of oxygen vacancy defects).
[0079] In step S22, after sintering, the N content of the ion sieve is controlled to be 1.5 at.% to 2.8 at.%, wherein the pyridine N accounts for 15% to 30%, and XPS analysis (ESCALAB 250) is performed.
[0080] After sintering in step S22, the size of the ion sieve is controlled to be about 150nm-200nm, and the specific surface area is 15.8m 2 / g~25.3m 2 / g.
[0081] S3, subjecting the product obtained in step S2 to acid washing.
[0082] The calcined powder obtained in step S2 is placed in any one of 0.1 mol / L to 0.5 mol / L hydrochloric acid, sulfuric acid or 2 mol / L to 8 mol / L sodium thiosulfate solution or a mixture of the two or more to obtain a titanium-based lithium adsorbent.
[0083] The present invention also provides the use of the adsorbent of any of the above embodiments in lithium precipitation mother liquor, lithium extraction from salt lake brine, or negative electrode materials for lithium ion batteries. That is, the adsorbent prepared by any of the above embodiments of the present invention can be used as an adsorbent for lithium precipitation mother liquor, lithium extraction from salt lake brine, or as a negative electrode material or modified material for lithium ion batteries.
[0084] The adsorbent and preparation method according to the embodiments of the present invention are described in detail below with reference to specific embodiments.
[0085] Example 1
[0086] Example 1 provides a titanium-based lithium ion sieve obtained by the following preparation method:
[0087] Weigh 3.47g of cerium nitrate hexahydrate and 0.86g of zirconium nitrate pentahydrate according to the molar ratio of Ce / Zr=0.8:0.2, and fully dissolve them in 100mL of deionized water and stir them to dissolve. Add the complexing agent ammonium citrate solution (ethanol dissolution, mass fraction 10%) dropwise, control the ratio of the total cerium zirconium content to the ammonium citrate concentration to be 1:1.2, and stir them fully. Place the resulting solution in a 90°C water bath for stirring and evaporation to obtain a yellow gel with a certain viscosity. Then place the gel in a 110°C blast drying oven and dry it for 12h to obtain a fluffy and porous dry gel, which is crushed and ground to obtain a cerium zirconium precursor.
[0088] Take 1.63 g of the above dry gel, add 1.2 g of rutile TiO2, 1.11 g of lithium carbonate, 0.025 g of PEG6000, and add 10 mL of ethanol to fully grind to obtain a mixed slurry.
[0089] The obtained slurry was dried at 60°C for 4 hours and then taken out and placed in a crucible for calcination. First, the temperature was raised to 250°C at a heating rate of 4°C / min in an air atmosphere and calcined at a constant temperature for 3 hours. Then, the temperature was raised to 500°C at a heating rate of 2°C / min in a nitrogen atmosphere and calcined for 10 hours. After cooling and grinding, the cerium-zirconium solid solution doped lithium metatitanate adsorption material Li2Ti 0.76 O3 / 0.24Ce 0.8 Zr 0.2 O2.
[0090] Li2Ti 0.76 O3 / 0.24Ce 0.8 Zr 0.2 O2 product characteristics are I 603 / I 465 =0.25, N content is 1.8at.%, of which pyridine N accounts for 25.7%, the average particle size of the product is about 158nm, and the specific surface area is 23.5m 2 / g; the contact angle between the powder material and 0.05M LiOH aqueous solution is 14°. The powder material is placed in a 0.25mol / L hydrochloric acid solution and soaked for 30 hours, centrifuged and washed to neutral for use. The adsorption and desorption of the material are shown in Table 2.
[0091] Example 2
[0092] Example 2 provides a titanium-based lithium ion sieve obtained by the following preparation method:
[0093] 3.91 g of cerium nitrate hexahydrate and 0.40 g of ferric nitrate nonahydrate were weighed according to the molar ratio of Ce / Fe=0.9:0.1, 2.16 g of urea were added, and the mixture was thoroughly ground and mixed to obtain an emulsion with uniform color, which was then placed in an oven at 80°C and dried overnight to obtain a ferrocerium precursor.
[0094] Take 0.59 g of the above precursor, add 1.2 g of anatase TiO2, 0.36 g of lithium hydroxide, 0.032 g of ammonium citrate, and add 10 mL of ethanol to fully grind to obtain a mixed slurry.
[0095] The obtained slurry was dried at 60°C for 4 hours and then taken out and placed in a crucible for calcination. First, the temperature was raised to 250°C at a heating rate of 4°C / min in an air atmosphere and calcined at a constant temperature for 3 hours. Then, the temperature was raised to 500°C at a heating rate of 2°C / min in an argon atmosphere and calcined for 10 hours. After cooling and grinding, the cerium-zirconium solid solution doped lithium metatitanate adsorption material Li2Ti 0.92 O3 / 0.08Ce 0.9 Fe 0.1 O2.
[0096] Li2Ti 0.92 O3 / 0.08Ce 0.9 Fe 0.1 O2 product characteristics are I 603 / I 465 =0.14, N content is 0.8at.%, of which pyridine N accounts for 14.1%, the average particle size of the product is about 180nm, and the specific surface area is 13.5m 2 / g; the contact angle between the powder material and 0.05M LiOH aqueous solution is 22°. The powder material is placed in a 0.25mol / L hydrochloric acid solution and soaked for 30 hours, centrifuged and washed to neutral for use. The adsorption and desorption of the material are shown in Table 2.
[0097] Example 3
[0098] This embodiment provides a titanium-based lithium ion sieve, which is obtained by the following preparation method:
[0099] 3.04 g of cerium nitrate hexahydrate, 0.47 g of calcium nitrate tetrahydrate and 0.30 g of indium nitrate were weighed and placed in 100 mL of deionized water according to the molar ratio of Ce / Ca / In=0.7:0.2:0.1, and stirred and dissolved. The complexing agent ammonium citrate solution (ethanol dissolution, mass fraction 10%) was added dropwise to control the total cerium zirconium content and ammonium citrate concentration ratio to be 1:1.2, and stirred thoroughly.
[0100] The obtained solution was placed in a water bath at 90°C for stirring and evaporation to obtain a yellow gel with a certain viscosity. The gel was then placed in a forced air drying oven at 110°C for 12 hours to obtain a fluffy and porous dry gel, which was crushed and ground to obtain a cerium calcium indium precursor.
[0101] 1.98 g of the above dry gel was taken, mixed with 1.74 g of metatitanic acid, 1.04 g of lithium nitrate, and 0.03 g of polyvinyl alcohol, and 10 mL of ethanol was added and fully ground to obtain a mixed slurry.
[0102] The obtained slurry was dried at 60°C for 4 hours and then taken out and placed in a crucible for calcination. First, the temperature was raised to 250°C at a heating rate of 4°C / min in an air atmosphere and calcined at a constant temperature for 3 hours. Then, the temperature was raised to 500°C at a heating rate of 2°C / min in an argon atmosphere and calcined for 10 hours. After cooling and grinding, the cerium-zirconium solid solution doped lithium metatitanate adsorption material Li2Ti 0.81 O3 / 0.19Ce 0.7 Ca 0.2 In 0.1 O2.
[0103] Li2Ti 0.81 O3 / 0.19Ce 0.7 Ca 0.2 In 0.1 O2 product characteristics are I 603 / I 465 =0.18, N content is 1.2at.%, of which pyridine N accounts for 13.5%, the average particle size of the product is about 165nm, and the specific surface area is 13.5m 2 / g; the contact angle between the powder material and 0.05M LiOH aqueous solution is 19.1°. Then, the powder material is immersed in 0.25mol / L hydrochloric acid solution for 30h, centrifuged and washed to neutral for use. The adsorption and desorption of the material are shown in Table 2.
[0104] Comparative Example 1
[0105] Comparative Example 1 provides a titanium-based adsorption material: solid powder CeO2 and ZrO2 are used as doping sources (Ce / Zr=0.8:0.2), and the preparation method of Example 1 is followed, except that the calcination stage directly adopts the heating rate of 4°C / min in air atmosphere to 500°C and calcined for 10h. 0.76 O3-mixed-0.24Ce 0.8 Zr 0.2 O2, product feature is I 603 / I 465 =0.045, N content is 0at.%, average particle size is about 295nm, specific surface area is 4.3m 2 / g; the contact angle between it and 0.05M LiOH aqueous solution is 30.5°. The adsorption and desorption conditions are shown in Table 2.
[0106] Comparative Example 2
[0107] Comparative Example 2 provides a titanium-based adsorption material. According to the method of Example 1, the Ce element is doped into the Li2TiO3 adsorption material. The difference is that 0.65g of cerium nitrate hexahydrate, 1.08g of rutile phase TiO2, 1.11g of lithium carbonate, and 0.025g of PEG6000 are directly weighed, and 10mL of ethanol is added to fully grind to obtain a mixed slurry. Similarly, after the slurry is dried, it is directly heated to 500°C at a heating rate of 4°C / min in an air atmosphere and calcined for 10 hours. The material Li2Ti 0.76 O3-mixed-0.24CeO2, product characteristics are I 603±0.2 / I 465±0.2 =0.33, N content is 1.6at.%, of which pyridine N accounts for 10.3%, the particle size is about 190.3nm, and the specific surface area is 19.6m 2 / g; the contact angle between it and 0.05M LiOH aqueous solution is 20.4°. The adsorption and desorption conditions are shown in Table 2.
[0108] Comparative Example 3
[0109] Comparative Example 3 provides a titanium-based adsorption material. According to the method of Example 2, the ferrocerium precursor preparation step is removed, and 0.15g urea, 1.2g anatase phase TiO2, 0.36g lithium hydroxide, and 0.032g ammonium citrate are directly added, and 10mL ethanol is added to fully grind to obtain a mixed slurry. The drying and calcination processes are the same as those of Example 2. The obtained material N-Li2Ti 0.92 O3, the product's I 603 / I 465 =0, indicating that the material is not doped with oxygen-deficient cerium-based materials, and the oxygen-deficient structure of the material itself is negligible. The product features a N content of 0.8 at.%, of which pyridine N accounts for 14.1%, a particle size of about 187.2 nm, and a specific surface area of 21.3 m 2 / g; the contact angle between it and 0.05M LiOH aqueous solution is 18.0°, and the adsorption and desorption conditions are shown in Table 2.
[0110] The titanium-based lithium adsorbent of the cerium-based solid solution material without oxygen body defects was prepared by the method of the above embodiment and comparative example, and the lithium adsorption performance of the titanium ion sieve obtained by the above embodiment and comparative example was tested by experiment. The specific method was to add 0.5g of the obtained material to 100mL 0.05mol / L lithium hydroxide solution and stir for 3h. After centrifugation and filtration of the supernatant at different times, the concentration of Li and Ti in the solution was measured by ICP to determine the maximum Li adsorption amount, equilibrium time and Ti dissolution rate. The product characteristics of each embodiment and comparative example are shown in Table 1, and the evaluation results are shown in Table 2 below.
[0111] Table 1 Product properties
[0112] Table 2 Experimental results
[0113]
[0114] It can be seen from Table 2 that the first equilibrium lithium adsorption capacity of the products in Examples 1 to 3 is not less than 31.2 mg g -1 , while the first equilibrium lithium adsorption amount of the products of Comparative Examples 1 to 3 was no more than 20.1 mg g -1 That is to say, the first equilibrium lithium adsorption amount of the products in Examples 1 to 3 is greater than the first equilibrium lithium adsorption amount of the products in each comparative example.
[0115] Moreover, the first equilibrium time of Examples 1 to 3 is no more than 170 min, while the first equilibrium time of Comparative Examples 1 to 3 is no less than 200 min, that is, the first equilibrium time of Examples 1 to 3 is shorter than the first equilibrium time of each comparative example.
[0116] Combined with the comparison results of the first equilibrium lithium adsorption amount and the first equilibrium time, it can be seen that the titanium-based lithium adsorbent of the embodiment of the present invention can effectively improve the lithium ion adsorption rate while ensuring the adsorption capacity, and greatly shorten the time required to reach adsorption equilibrium.
[0117] Moreover, the equilibrium adsorption capacity of the products of Examples 1 to 3 after 20 cycles is not less than 21.8 mg g -1 The equilibrium adsorption capacity of the products of Comparative Examples 1 to 3 after 20 cycles is no more than 14.1 mg g -1 It can be seen that the equilibrium adsorption amounts of the products of Examples 1 to 3 after 20 cycles are greater than the equilibrium adsorption amounts of the products of the comparative examples after 20 cycles, that is, the products of the embodiments of the present invention still have a relatively high adsorption capacity after multiple cycles of adsorption-desorption experiments.
[0118] The results of Examples 1 to 3 show that the lithium adsorption capacity is higher than 30 mg g -1 , the equilibrium time is shortened to within 150min-170min, and the first dissolution loss rate of titanium is reduced to less than 1.5%. From the results in Table 2, it can be seen that the reduction in the amount of adsorption after the cycle is relatively low overall, and the dissolution loss of titanium is also relatively low. It can be seen that the titanium-based lithium ion sieve of the present invention is an oxygen-defect solid solution-type ion sieve, which can effectively improve the diffusion rate of lithium inside and outside the adsorbent. In addition, the ion sieve formed by acid washing in each embodiment has good acid corrosion resistance and structural stability, and good overall adsorption performance.
[0119] In addition, the electron microscope image corresponding to Comparative Example 3 is as follows Figure 1 As shown, the electron microscope image corresponding to the product of Example 1 is as follows Figure 2 As shown in the figure, it can be seen that without adding cerium, the particle size of the precursor Ti-based adsorbent is generally larger ( Figure 1 ); After adding the cerium-based oxygen defect solid solution material, the adsorbent material particles obtained are more evenly distributed and smaller in size, so the adsorption rate is faster during the lithium adsorption process.
[0120] In summary, the present invention firstly introduces the cerium-based precursor by the sol-gel method or the solution combustion method, and can reasonably use the ion radius effect or the valence balance theory to simultaneously introduce other metal elements, and form a solid solution with lattice oxygen defects and a composite structure of Li2TiO3 in the subsequent roasting process. When organic species (ammonium citrate or urea) exist in the precursor, the temperature required for roasting can be reduced, and the operation is simple and convenient. The obtained adsorbent not only has a small particle size and is evenly distributed, but also has good structural stability of the ion sieve acid corrosion resistant agent formed by acid washing, and has a longer cycle service life.
[0121] At the same time, the decomposition of the cerium-based precursor organic matter can provide the adsorbent with rich nitrogen functional groups and porous structures, further improving the wettability of the adsorbent to the lithium-rich solution. More importantly, the doping of the cerium-based solid solution material rich in oxygen defects can reduce the diffusion barrier of lithium ions and accelerate the Li+ in the solid phase. + transfer, promoting the improvement of lithium adsorption rate. Therefore, the preparation method of the present invention can synergistically achieve the reduction of the calcination temperature of the titanium-based ion sieve and the effective improvement of the lithium adsorption rate in one step. Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are only for illustration and not for limiting the scope of the present invention. Those skilled in the art should understand that the above embodiments can be modified without departing from the scope and spirit of the present invention. The scope of the present invention is defined by the appended claims.
Claims
1. A titanium-based lithium ion sieve, characterized in that: Include: Lithium titanium oxide, and a cerium-based solid solution, wherein the cerium-based solid solution contains oxygen vacancies, and in the Raman spectrum of the cerium-based solid solution, at 464.8 cm -1 ~465.2cm -1 and 602.8cm -1 ~603.2cm -1 The ratio of the peak intensity at I 603±0.2 / I 465±0.2 =0.05~0.
3.
2. The titanium-based lithium ion sieve according to claim 1, characterized in that: The cerium-based solid solution dopes the lithium titanium oxide.
3. The titanium-based lithium ion sieve according to claim 1, characterized in that: The molecular formula of the titanium-based lithium ion sieve is Li2Ti x O3 / (1-x)Ce y M 1-y O2, wherein M is a metal element that forms a solid solution with the cerium-based material, and x and y represent the molar ratio of the elements: x=0.7-0.9, y=0.6-0.
95.
4. The titanium-based lithium ion sieve according to claim 1, characterized in that: The titanium-based lithium ion sieve contains nitrogen element, and the content of the nitrogen element in the titanium-based lithium ion sieve is 1.5at.% to 2.8at.%; and / or the titanium-based lithium ion sieve contains pyridinic nitrogen, and the pyridinic nitrogen accounts for 15% to 30% of the total nitrogen content.
5. The titanium-based lithium ion sieve according to claim 1, characterized in that: The average particle size of the titanium-based lithium ion sieve is 150nm to 200nm; and / or the specific surface area is 15.8m 2 / g~25.3m 2 / g; and / or, a contact angle with a 0.05M LiOH aqueous solution of 14° to 28°.
6. A method for preparing a titanium-based lithium ion sieve, characterized in that: The steps include: mixing a cerium-based precursor, a titanium source and a lithium source to obtain a solid phase mixture; The solid phase mixture is calcined to obtain a titanium-based lithium ion sieve, wherein the titanium-based lithium ion sieve comprises lithium titanium oxide and a cerium-based solid solution, wherein the cerium-based solid solution comprises oxygen vacancies, and in the Raman spectrum of the cerium-based solid solution, at 464.8 cm -1 ~465.2cm -1 and 602.8cm -1 ~603.2cm -1 The ratio of the peak intensity at I 603±0.2 / I 465±0.2 =0.05~0.
3.
7. The method for preparing the titanium-based lithium ion sieve according to claim 6, characterized in that: The roasting adopts the step-by-step firing process.
8. The method for preparing the titanium-based lithium ion sieve according to claim 6, characterized in that: The preparation method of the cerium-based precursor adopts a sol-gel method or a solution combustion method, and nitrogen doping is performed by providing a nitrogen-containing environment.
9. The method for preparing the titanium-based lithium ion sieve according to claim 6, characterized in that: The cerium-based solid solution is a composite solid oxide composed of Ce and one or more of Ca, Mg, Ni, Co, Zn, La, In, Fe and Zr; and / or, the titanium source is one or more of anatase titanium dioxide, rutile phase titanium dioxide, mixed phase titanium dioxide and metatitanic acid; and / or, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium nitrate, lithium acetate and lithium citrate.
10. The method for preparing the titanium-based lithium ion sieve according to claim 6, characterized in that: The following steps are also included: The titanium-based lithium ion sieve is acid washed.
Citation Information
Cited By
Composite lithium ion sieve and preparation method and application thereof
CN122183547A
A composite lithium-ion sieve, its preparation method and application
CN122183547B
A multidimensional composite, three-point doped titanium-based lithium-ion adsorbent and its preparation method
CN122558420A